Ultra-wideband and high-efficiency polarization rotator based on liquid crystals - Sang-Hee Lee; Chan-Hee Han; Seung-Won Oh (Journal of Information Display)
We propose a novel design of an asymmetrically anchored negative liquid crystal (LC) cell capable of linearly rotating the polarization axis of broadband light, with the rotation angle controlled by voltage. Unlike conventional LC cells that require polarization filters or retarders, our LC cell can directly modulate the polarization state of light without any additional components. The LC cell exhibits high polarization rotation efficiency over a wide wavelength range (200 nm to 2000nm), superior to the existing polarization modulators. We validate our design through theoretical calculations and numerical simulations, proving that a degree of linear polarization of over 0.95 can be achieved in the UV, visible, and NIR regions. Our design can be applied in optical communications, biological imaging, and spectroscopic technologies.